Gen 4 bei Flavius Josephus - Erzberger, Johanna (Protokolle zur Bibel, 2008)
The order of nature is a central element of Josephus’ „ideology“, that expresses itself in Josephus’ interpretation of biblical texts, but to which modern readers have no other direct access. Moses’ order and the ἐπιτηδεύμα of Judaism fulfill it in an ideal way. While Abel lives according to the order of nature, Cain forces his order on society and world. Cain’s ἐπιτηδεύμα corresponds to the condition of the world after the end of the golden age. Education enables some kind of ἐπιτηδεύμα according to the order of nature even after the end of the golden age. Against that setting Cain as anti-παιδαγωγός faces the παιδαγωγός God. LXX and rabbinic traditions represent alternative ways of reading and understanding according to another „ideology“ and worldview.